PELATIHAN DAN PENDAMPINGAN BUDIDAYA OKRA MODERN PADA KELOMPOK WANITA TANI DI KELURAHAN SIALANGMUNGGU - Arini, Arini; Tegar Firmansyah; Arsel, Aditya Dwitama; Altia Pawistri; Aditya Firmansyah; Tajri Natra; Fitrah Hidayah; M Zais; Nugraha, Danuarta; Ningsih, Cindi Rahayu; Ferro Nika Ningsih N, Putri Dwi; Kurniawan, Nauri; Milanda Putri, Aprilia; Siti Minarti (Komunitas Manajemen Kompetitif, 2025)
The training and mentoring program on modern okra (Abelmoschus esculentus) cultivation was conducted in Sialangmunggu Village, Tuah Madani District, Pekanbaru City, to enhance the knowledge and skills of local communities who still relied on traditional farming methods. The program focused on the selection of superior seeds, proper land management, effective planting techniques, and pest and disease control, which were delivered to women farmer groups and local residents. The results indicated an improvement in participants’ understanding of the importance of using quality seeds, appropriate land preparation, and effective pest management strategies, enabling the community to apply modern and efficient okra cultivation practices to support sustainable agricultural productivity